Modelling of beyond budgeting, competitor accounting, transparency, competitive advantage, and organizational performance: The case of Indonesia SMEs - Harbi Valdiansyah, Riyan; Augustine, Yvonne (Technium Social Sciences Journal, 2021)
SMEs are the backbone in driving the Indonesian economy and play an essential role in creating jobs throughout Indonesia. Indonesian SMEs are the key to designing inclusive development through the merger of large & small businesses so that economic equity can touch all levels of society. This study examines several factors of Indonesian SMEs’ organizational performance, such as beyond budgeting, competitor accounting, and transparency through competitive advantage. This research was conducted by distributing online questionnaires to business owners, financial managers, or financial supervisors of SMEs in Indonesia spread across six islands. A total of 155 questionnaires were obtained in this study and analysed by SMART PLS 3.2.9. The results show that beyond budgeting and transparency influence competitive advantage, while competitor accounting does not. Other results show that competitor accounting, transparency, and competitive advantage influence business performance, while beyond budgeting does not. Path analysis in this study shows that competitive advantage mediates beyond budgeting and transparency, while competitor accounting is not mediated. Researchers are aware that this study has limitations in data dissemination and was distributed during the COVID-19 pandemic conditions, which allowed for differences in results with other similar studies. Hopefully, with this research that practitioners will be able to provide other views beyond budgeting, competitor analysis, and the side of transparency for Small and Medium Enterprises in Indonesia. Policymakers can encourage SMEs to be more innovative and responsive to science through programs to increase business scale, considering the contribution of SMEs to Indonesia’s gross domestic product. Further research is expected to analyze more deeply what factors affect the competitive advantage and organizational performance of small and medium enterprises, such as the availability of working capital, SME access to banks, how digitalization plays a role, etc.